Two Doctors, One Patient, and a Common Goal - Nabhan, Chadi (Oncologist, 2018)
Navigating end‐of‐life care is never easy. In this narrative, two physicians collaborate to convey the emotional strain and unique perspectives of different specialists caring for the same patient at the end of life.